Ideologi dan Propaganda dalam Memperkuat Perlawanan di Revolusi Amerika - Ramadhan, Rizky; Esra, Setia; Aprilia A, Annisa; Nidarwati G, Winda; Dalimunthe, Sadina Yanti; Marpaung, Adrian; Tarigan, Adolf (Polyscopia, 2024)
The American Revolution was a seminal moment in history defined not only by military action but also by the effective use of ideology and propaganda. This research explores the role of Enlightenment ideology and propaganda in strengthening resistance to British colonial rule. Ideas about human rights and government based on the consent of the governed became the philosophical basis for the revolutionary struggle, while propaganda through pamphlets, newspapers, speeches, and visual symbols spread these messages to the wider public. By utilizing effective propaganda, revolutionary leaders succeeded in mobilizing domestic support and attracting international aid, particularly from France. Visual propaganda, such as illustrations of the Boston Massacre and passionate public speeches, played an important role in building solidarity and motivation among the colonists. The findings show that ideology and propaganda are powerful tools in shaping public opinion and mobilizing the masses for revolutionary goals. The American Revolution illustrates how major historical changes often begin with shifts in thought and communication.